Genipin-mediated immobilization of glucose oxidase enzyme on carbon felt for use as heterogeneous catalyst in sustainable wastewater treatment. Issue 4 (August 2021) - Kahoush, May; Behary, Nemeshwaree; Guan, Jinping; Cayla, Aurélie; Mutel, Brigitte; Nierstrasz, Vincent
Abstract: Enzyme immobilization is necessary process to improve the bioactivity and stability of the biocatalyst. In this study, glucose oxidase (GOx) enzyme was immobilized on plasma-treated fibrous carbon felt as a textile carrier to produce a heterogeneous catalyst. Genipin, as a naturally occurring crosslinker, that has less cytotoxicity than conventional crosslinkers, was used in the enzyme immobilization process. UV-Vis and FTIR spectra confirmed the crosslinking reaction between genipin and the primary amines of GOx enzyme, by forming blue-pigmented aggregates. GOx relative activity after crosslinking and immobilization on the carbon felt was maintained up to 40%, with stability in performance up to 6 cycles for the plasma treated carbon, while maintaining their bio-electro-activity as shown from cyclic voltammetry scans (CV). The obtained heterogeneous catalysts have been tested for use in sustainable wastewater treatment of Remazol Blue RR (RB) dyestuff by means of Bio-Fenton (BF) and enzymatic Bio-electro-Fenton (BEF) processes. The produced samples resulted in high color removal efficiency, up to 93% discoloration of (RB) for the first use in (BF) process in 3 h. Meanwhile, enzymatic (BEF) process resulted in up to 34% of COD removal, with simultaneous power density generation up to 0.16 ± 0.01 μW.cm −2 at a current density of around 10 ± 2 μA.cm −2 in 12 h. These results highlight the importance of genipin as a bio-based crosslinker for enzymes, and the potential use in both (BF) and (BEF) as sustainable approaches for wastewater treatment and as a step towards zero-energy degradation of organic matter. Graphical Abstract: ga1 Highlights: Genipin has potential as bio-based direct crosslinker of GOx enzyme on carbon felt. The heterogeneous catalyst was used in sustainable wastewater treatment. Discoloration and COD removal of Remazol blue were reported using the catalyst. Simultaneous power generation was achieved by enzymatic Bio-electro-Fenton setup.